1989
DOI: 10.1017/s000335610000427x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of milk consumption curve parameters for different genetic groups of bovine calves

Abstract: Milk consumption was estimated for crossbred suckled calves from birth to weaning during 2 years. Breed groups utilized were Aberdeen Angus (A) and Charolais (C) sires on Fl Angus-Hereford (and their reciprocals) dams in the 1st year and in the 2nd year, sires A and Nelore (Bos indicus) (N) were used on the same type of dam. The weigh-suckle-weigh technique was employed twice a day to estimate milk consumption on a weekly basis. Estimations were adjusted by least-squares for the effects of genetic group, week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The estimate of 5.5% observed in this study was within the range of 2.76 to 14.5% reported for beef cattle by Marshall et al (1976), Gregory et al (1992), and Kress et al (1992). Johnston et al (1995) reported an average 32% heterosis for Cow MY (Butson and Berg, 1984;Mezzadra et al, 1989;McCarter et al, 1991). With heterozygosity of the calf affecting calf growth, an effect of heterosis of the calf on Calf MY would be expected.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The estimate of 5.5% observed in this study was within the range of 2.76 to 14.5% reported for beef cattle by Marshall et al (1976), Gregory et al (1992), and Kress et al (1992). Johnston et al (1995) reported an average 32% heterosis for Cow MY (Butson and Berg, 1984;Mezzadra et al, 1989;McCarter et al, 1991). With heterozygosity of the calf affecting calf growth, an effect of heterosis of the calf on Calf MY would be expected.…”
Section: Resultssupporting
confidence: 78%
“…Similarly, milk yield of the cow can be considered as a trait influenced by the calf and the cow. The calf can influence milk yield of the cow through demand for milk and nursing frequency (Drewry et al, 1959;Mezzadra et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, Wokalup dams potentially produced more milk than the calves could drink in the suckling period allowed. Mezzadra et al (1989) reported differences in lactation curves of crossbred cows suckling Bos indicusand Bos taurus-sired calves, the former peaking earlier during lactation and showing less persistency.…”
Section: Discussionmentioning
confidence: 99%
“…1971 b). Mezzadra et al (1989) reported than Charolals calves caused their crossbred dams to produce more milk than Angus calves. found that Angus cows produced 20% (P < .05) more milk when their calves were crossbred.…”
Section: Breed Of Calf and Milk Production Calf Gain And Weaning Weightmentioning
confidence: 99%